Activation of ERK Signaling via TLR11 Induces IL-12p40 Production in Peritoneal Macrophages Challenged by Neospora caninum - Jin, Xiaoxia; Gong, Pengtao; Zhang, Xichen; Li, Guojiang; Zhu, Tao; Zhang, Mengge; Li, Jianhua (Frontiers in Microbiology, 2017)
Neospora caninum, an obligate intracellular protozoan parasite, can infect a large variety of vertebrate hosts including the most economically important cattle. Infection with N. caninum is a main cause of abortion in both dairy and beef cattle, which causes great economic losses worldwide. However, the mechanism of host cell infection by N. caninum has not been fully elucidated, especially in terms of inflammatory responses. In this study, the effect of TLR-ERK signaling pathway on the synthesis of pro-inflammatory interleukin-12p40 in mouse peritoneal macrophages (PMϕ) challenged by N. caninum was investigated. Our results suggested that N. caninum infection quickly activated MEK-ERK signaling via TLR11 in PMϕ. In addition, N. caninum infection also caused upregulated production of IL-12p40 by PMϕ, which was significantly reduced with the blockade of TLR11/MEK/ERK pathway, suggesting that this upregulation of IL-12 p40 was TLR11 and MEK-ERK-activation dependent.